Effects of supplementation with crystalline or coated methionine and lysine in low protein diet on growth performance, intestinal health and muscle quality of gibel carp, Carassius auratus gibelio - Lin, Xiaowen; Du, Yingying; de Cruz, Clement; Zhao, Jianhua; Shao, Xianping; Xu, Qiyou (Elsevier, 2024)
A 10-week feeding trial was conducted to elucidate the effects of coated amino acids on growth performance, intestinal health, and muscle quality of gibel carp (Carassius auratus gibelio) fed with low protein diet. A total of 450 carps (initial body weight of 15.67 g ± 0.04) were selected and randomly assigned into 6 groups, with each group consisting of three replicates and 25 fish per replicate. Six experimental diets were: control group (NP, 31.44% CP), low protein group (LP, 28.69% CP), low protein supplemented with crystalline methionine (CrM), crystalline methionine and crystalline lysine (CrML), coated methionine (CoM) or coated methionine and coated lysine (CoML). The results indicated that compared to the NP group, the LP group showed no significant difference in weight gain, specific growth rate, feed conversion ratio, viscerosomatic index, and condition factor (P > 0.05) but had a significant decrease in whole body crude fat content and increase in moisture content (P < 0.05). The hepatosomatic index in the CoML group was significantly lower than the LP group (P<0.05), and moisture content in the CrM and CoM groups was significantly lower than LP group (P<0.05). Serum alanine transaminase of the CrML group was significantly lower than the LP group. Methane dicarboxylic aldehyde content and superoxide dismutase activity in the CrML group were significantly lower than those in the LP group (P<0.05), and hardness, firmness, and chewiness in the CoM group were significantly lower (P<0.05) than the LP group. Compared to crystalline amino acids, coated amino acid groups showed a significant increase in crude fat content (P<0.05) and significant enhancements in the activities of superoxide dismutase and catalase (P<0.05). This results indicate that low protein feed supplemented coated amino acids can significantly improve the antioxidant capacity, fat deposition, intestinal health, and muscle quality of gibel carp. © 2024 The Authors